A hydromechanical FEM fracturing simulator under the leak-off phenomenon perspective - Roseno, Karina Tamião de Campos; Poli, Renato; Cleto, Pedro Rogério [UNESP]; Carrion, Ronaldo (Taylor & Francis, 2023)
Carter’s model of fluid loss is used in the oil and gas industry performing the numerical approach of leak-off. Its deduction applies some simplifying assumptions, such as the difference between fluid pressure and constant pore pressure and filtration process approximation to a unidirectional flow, perpendicular to the fracture plane. For this paper, the so-called Chimas is an hydromechanical simulator of oil reservoirs, fully coupled and implicit, in a way that considers the poroelastic effects on the propagation of fractures. The leak-off process is explicitly treated in the fracture boundary conditions using Darcy’s law. The objective of this work is to validate the filtration phenomenon of Chimas hydromechanical simulator comparing the parameters of length, width and injection pressure with those obtained using an iterative method implemented in MatLab and which includes Carter’s analytical equation. Numerical accuracy was validated against asymptotic analytical solutions. The agreement between the iterative method and the analytical solutions was particularly good in relation the length fracture and injection pressure.
Keywords: Carter equation; finite element method; fracture extension; fracture mechanics; leak-off; rock mechanics